2018
DOI: 10.1002/ejp.1251
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone‐related peptide activates and modulates TRPV1 channel in human DRG neurons

Abstract: Parathyroid hormone-related peptide (PTHrP) is associated with advanced tumor growth and metastasis, especially in breast, prostate and myeloma cancers that metastasize to bones, resulting in debilitating chronic pain conditions. Our recent studies revealed that the receptor for PTHrP, PTH1R, is expressed in mouse DRG sensory neurons, and its activation leads to flow-activation and modulation of TRPV1 channel function, resulting in peripheral heat and mechanical hypersensitivity. In order to verify the transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This signalling axis requires further research, particularly exploring the inhibition of PTHrP and its potentially analgesic effect on multiple myeloma-induced bone pain. Furthermore, the experiment confirmed the presence of this axis in humans after the initial identification in mice, this result, therefore, gives researchers confidence that this can be explored in in-vivo models with therapeutic intent, with the suggestion that findings in mice will translate into human models effectively [16].…”
Section: Consequences Of Increased Osteoclast Activitymentioning
confidence: 52%
See 1 more Smart Citation
“…This signalling axis requires further research, particularly exploring the inhibition of PTHrP and its potentially analgesic effect on multiple myeloma-induced bone pain. Furthermore, the experiment confirmed the presence of this axis in humans after the initial identification in mice, this result, therefore, gives researchers confidence that this can be explored in in-vivo models with therapeutic intent, with the suggestion that findings in mice will translate into human models effectively [16].…”
Section: Consequences Of Increased Osteoclast Activitymentioning
confidence: 52%
“…The confirmation of this pathway in humans was achieved by immunohistochemistry and calcium ion imaging on human dorsal root ganglions. This pathway, therefore, presents a potential therapeutic target to modulate the pain experienced from the breakdown of bone in an environment of pH below six [16].…”
Section: Parathyroid Hormone-related Peptidementioning
confidence: 99%
“…Consistently, NHERF2 was not detected in ROS 17/2.8 cells, a rat osteoblastic line 38 . Recent work reported that activation of PTHrP/PTH1R mediated signaling in cultured human DRGs was suggested to be involved in peripheral heat and mechanical hypersensitivity 39 , suggesting opposite neural function of PTHrP and PTH although they share the same receptor; PTH1R. Their binding preferences to different conformations of PTH1R may cause distinct neuronal function as proposed in osteoblast lineage cells 40 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, E-selectin is considered as an effective adjuvant therapeutic drug to disrupt the interaction between cancer cells and bone marrow, especially in the cancers metastasizing to the bone, stressing the importance of regulating bone marrow microenvironment in inhibiting bone metastases (Muz et al, 2021). Additionally, PTH-related peptide is highly related to bone metastasis and leads to chronic pain in patients (Shepherd et al, 2018). While it is also worth noticing that metastasized cancer cells produce PTH-related peptide to induce RANKL, thus accelerating bone resorption, in turn, bone resorption further stimulates the release of tumor growth factors, resulting in promotion of tumor growth in bone and bone metastasis (Takayanagi, 2020).…”
Section: Cancermentioning
confidence: 99%